2013
DOI: 10.1111/jan.12275
|View full text |Cite
|
Sign up to set email alerts
|

Young adult women's experiences of body image after bariatric surgery: a descriptive phenomenological study

Abstract: Perception of control may be an essential aspect of body image and the key to understanding these young women's feelings of empowerment and quality of life through body control postbariatric surgery. Future studies should focus on how body control is an essential aspect of body image, which may contribute to long-term weight loss maintenance and improve quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
0
13

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(61 citation statements)
references
References 46 publications
(61 reference statements)
3
44
0
13
Order By: Relevance
“…More recently, the male's ideal body size and image have been made more visible in society and men are aspiring to a perfect body shape (Grogan, 2007). Women's decisions to undergo bariatric surgery are typically motivated by concerns about their appearances and, in general, women seeking bariatric surgery have a lowered body satisfaction compared with men (Jensen et al, 2013). Similar to previous research findings, the men in this study identified body image concerns, which in some cases were minimized by them, where they identified that their primary motivation was to improve their health in the first instance.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…More recently, the male's ideal body size and image have been made more visible in society and men are aspiring to a perfect body shape (Grogan, 2007). Women's decisions to undergo bariatric surgery are typically motivated by concerns about their appearances and, in general, women seeking bariatric surgery have a lowered body satisfaction compared with men (Jensen et al, 2013). Similar to previous research findings, the men in this study identified body image concerns, which in some cases were minimized by them, where they identified that their primary motivation was to improve their health in the first instance.…”
Section: Discussionsupporting
confidence: 78%
“…Research suggests that men are motivated to have surgery to improve both their current and future health status, where women are mostly concerned with improving their body image (Jensen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Qualitative studies can provide powerful and scientifically rigorous research findings27 and have been used widely to investigate the impact of chronic illness from the patient's perspective 28 29…”
Section: Discussionmentioning
confidence: 99%
“…Em pacientes obesos com comorbidades associadas, a manutenção da perda de peso através dos tratamentos convencionais é uma tarefa difícil de se realizar e indivíduos com obesidade grave não podem simplesmente confiar nos resultados dos métodos convencionais para o tratamento da obesidade como um meio de manter a perda de peso a longo prazo (1,2). Assim, quando esses métodos não são eficazes, surge a necessidade de uma intervenção cirúrgica para solucionar o problema do excesso de peso, denominada de cirurgia bariátrica (3).…”
Section: Introductionunclassified